DEVELOPMENT OF GRAPE CULTIVATION AS AN EFFORT TO INCREASE COMMUNITY INCOME IN GEULUMPANG VILLAGE, SULU TIMU - Yanita, Yanita; Rusydi, Rusydi; Yusuf Iis, Em; Subhan, Subhan (RADJA PUBLIKA, 2022)
The aim of this research is to carry out counseling, training and assistance on grape cultivation techniques to the people of Geulumpang Sulu Timu so that they have expertise in plant cultivation and improve skills that are able to move young people around to become entrepreneurs in the production and marketing of wine. The methods used in this research are community empowerment methods, program implementation methods and activity roadmaps.In the end , the activities in the form of counseling and training as well as assistance in grape cultivation became a solution to improve the welfare of the people of Geulumpang, Sulu Timu .The training provided is up to a commercial level so that the resulting products can be marketed in traditional markets and supermarkets.